PENGARUH PROMOSI KESEHATAN MENGGUNAKAN VIDEO EDUKASI TERHADAP PENINGKATAN PENGATAHUAN IBU TENTANG IUD - Chadaryanti, Diyah; Susilawati, Dewi (Universitas Mohammad Husni Thamrin, 2022)
Background: IUD is one of the non-hormonal contraceptive methods and is considered an ideal long-term contraceptive method for spacing pregnancies. The advantages of using IUD include requiring only one insertion for a long period of time at a low cost, being safe as it does not have systemic effects on the body, not affecting breastfeeding, and allowing for quick return of fertility after removal. One of the factors contributing to the low usage of IUD contraception is the low level of knowledge among Women of Reproductive Age (WRA) regarding IUD contraception.Objective: The objective of this study is to determine the effectiveness of IUD contraception education through animated video media in increasing knowledge and attitudes among mothers of Childbearing Age (CBA).Research Methodology: The research method employed in this study is a Pre-Experimental Design using the One-Group Pretest-Posttest Design. The study was conducted at Pusyandu Susukan, East Jakarta, with a sample size of 45 individuals in Desember 2021. The health promotion media provided was in the form of a video about IUD.Results: The analysis revealed a significant difference in the level of knowledge among women of childbearing age before and after receiving health promotion, with a p-value of 0.000 (p < 0.05). It is recommended that women of childbearing age increase their knowledge about IUD contraception by attending health education sessions conducted by healthcare providers and seeking information about IUD contraception at nearby healthcare facilities. The Research Conducted on Desember 2021Conclusion and Recommendations: IUD contraception education through animated video media is effective in improving knowledge and attitudes among mothers of Childbearing Age (CBA). It is hoped that the community in Pucung Village, Pekalongan Regency, will continue their information dissemination activities through both individual and group health education sessions.Â Keywords: Health Promotion, IUD, Knowledge, Women of Reproductive AgeÂ